THESAURUS REQUIREMENTS GRAMMARS OF TURKIС LANGUAGES - Sharipbay, А.Ә; Razakhova, Б.Ш; Mukanova, А.С.; Zhetkenbay, Л. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This paper describes the requirements for thesaurus grammar of Kazakh language. Elements such as descriptors are considered, as well as terms from the synonymic series that is included in the thesaurus, called ascriptors or nondescriptors, and are used as auxiliary elements (text inputs) to help find suitable descriptors. The requirements for descriptors are also given. If the descriptor is formed by a phrase and the reference word is a noun, then one of the following conditions must be met. And examples are given for them. There are cases when it is not possible to find an unambiguous and clear descriptor, then the term that is taken as a descriptor is provided with a relator or comment. The semantic relationship between descriptors is described in detail. The main goals of establishing associative relations between descriptors are described. Definitions are given for each type of relationship.